Ideas of Poetics and the Close Reading of Poetry. Issue 1 (April 2018) - Hart, Jonathan Locke
Abstract : Ranjan Ghosh and J. Hillis Miller provide different but productive ways to think about poetics and to read poetry closely and with attention. As a poet, reader and critic of poetry, I welcome their thoughts on the theory and practice of poetry. Whereas Miller sees the reading of poems as subjective and selective, Ghosh views it as universal and shared. Both readers help us in the drama of meaning, the tension between them. As convivial and suggestive as that difference between Miller and Ghosh may be, it allows us to experience the different sides of poetry and the philosophy of poetry, if we think about, say the Socratic, Platonic, and Aristotelian tradition of thinking about poetry and even Philip Sidney's response on the one hand and the rhetorical tradition of reading poetry on the other. Ghosh, although having mastered Western literature and poetry, as Miller has, also provides us with Eastern views, and this is also of great benefit to the reader of Thinking Literature Across Continents (2016 ). One of the great centres of literature is language and poetry is compressed and memorable language that forms the heart of literature: it is a key to thinking about Ghosh and Miller thinking literature across the various parts of the world.